Novel Insights Into Epigenetic Reprogramming and Destabilization of Pericentromeric Heterochromatin in Cancer - Gjerstorff, Morten Frier (Frontiers in Oncology, 2020)
Pericentromeric heterochromatin is maintained in a condensed structure by repressive epigenetic control mechanisms and perturbation of these may cause diseases. The chromosome 1q12 region harbors the largest pericentromeric heterochromatin domain in the genome and is among the most common breakpoints in both solid and hematopoietic cancers. Furthermore, the 1q arm is frequently amplified in cancer and this may support tumorigenesis by increasing the dosage of the many oncogenes of this genomic region. Recent studies have provided insight into the mechanisms leading to loss of 1q12 stability and 1q amplification and DNA hypomethylation seems to play a prominent role. This may be the result of decreased activity of DNA methyltransferases and instrumental for 1q12 destabilization or arise secondary to perturbation of other important epigenetic mechanisms that control repression of pericentromeric heterochromatin. Polycomb proteins were recently demonstrated to epigenetically reprogram demethylated 1q12 pericentromeric heterochromatin in premalignant and malignant cells to form large subnuclear structures known as polycomb bodies. This may influence the regulation and stability of 1q12 pericentromeric heterochromatin and/or the distribution of polycomb factors to support tumorigenesis. This review will discuss recent insight into the epigenetic perturbations causing the destabilization of 1q12 pericentromeic heterochromatin and its possible implications for tumor biology.